Projects-to-think-with and projects-to-talk with: how adult learners experience project-based learning in an online course - Chen, Huei-Lien (Kansas State University, 2006)
In many college of education programs, the feasibility of online courses has provided opportunities for in-service teachers who are pursuing a higher educational goal while working full-time with school and/or family responsibilities. Although preliminary evidence on project-based learning (PBL) in traditional classrooms with younger learners suggests that students are highly motivated, it is not clear whether adult learners recognize the value of the online PBL approach. This study documented adult learners’ learning experience with online projects, their collaborative experience, and their learning experience with technological tools. The result of this study can contribute to our understanding of the strengths and the obstacles in an online PBL environment. Nineteen participants who registered in a graduate level course participated in this case study over a 16-week semester. They collaborated in small group of 2–5 members in order to communicate and construct projects at a distance. Qualitative and quantitative data were collected and interpreted based on a descriptive case study design. Multiple sources of data include course documentation, archival data from course management system, student-created projects, surveys, and interviews. A model for content analysis of CMC was applied to qualitative analysis of the electronic discourse. Findings of this study indicated that participants gained positive experience in this new way of learning. In particular, three themes related to online PBL approach emerged: (1) project relevancy and authenticity as the primary concerns in guiding driving question, researching information, and constructing artifact; (2) synchronicity is indispensable for online collaboration; and (3) repeated exposures with technology tools reduce the fear and reinforce the skill to be learned.
Keywords: Project-Based Learning; Online Collaboration; Technology; Virtual groups; Social space; Chatroom; Education, Curriculum and Instruction (0727); Education, Teacher Training (0530); Education, Technology (0710)